2019
DOI: 10.1101/19001917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reproducibility and transparency characteristics of oncology research evidence

Abstract: Introduction: As much as 50%-90% of research is estimated to be irreproducible, costing upwards of $28 billion in the United States alone. Reproducible research practices are essential to improving the reproducibility and transparency of biomedical research, such as including pre-registering studies, publishing a protocol, making research data and metadata publicly available, and publishing in open access journals. Here we report an investigation of key reproducible or transparent research practices in the pub… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This is reflected in our data, where preregistrations and registered reports were relatively more known, more positively evaluated, and more frequently used among ECRs from the HUM section than those from the BM and CPT sections. However, this could be likely to change in future years, with researchers from fields other than the social sciences calling for the implementation of preregistrations and registered reports to improve the transparency and reproducibility of their research fields (e.g., Parker et al, 2019 ; Walters et al, 2019 ). We further observed that ECRs across sections showed similarly low levels of participation in replication studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in our data, where preregistrations and registered reports were relatively more known, more positively evaluated, and more frequently used among ECRs from the HUM section than those from the BM and CPT sections. However, this could be likely to change in future years, with researchers from fields other than the social sciences calling for the implementation of preregistrations and registered reports to improve the transparency and reproducibility of their research fields (e.g., Parker et al, 2019 ; Walters et al, 2019 ). We further observed that ECRs across sections showed similarly low levels of participation in replication studies.…”
Section: Discussionmentioning
confidence: 99%
“…The reproducibility of systematic reviews, however, is very difficult if not impossible to undertake. The senior author of this study widely evaluates research reproducibility [41][42][43][44][45][46][47][48][49] and has evaluated the reproducibility of meta-analyses. 50 While meta-analytic effect estimates may be more reproducible in some cases, earlier steps of the systematic review process are likely not.…”
Section: Strengths and Limitationsmentioning
confidence: 99%